Enhancing Understanding and Application of Fundamental Visual Elements and Visual Principles Through Collaborative Learning: Insights from the Experiences of Design Students - Adhitama, Gregorius Prasetyo; Bhumi, Yogie Candra; Rahma , Miranti Sari; Agriyadi , Yuki; Simarmata, Andriano; Alfin, Eljihadi; Widasati , Arsaika; Hatmojo Danurdoro , Dwi; Saphiranti , Dona (Institut Seni Indonesia Denpasar, 2024)
Recent scholarly discussions have robustly endorsed collaborative learning in educational settings but also highlight a significant gap in understanding its effects, particularly in the design disciplines of Indonesian higher education. This research aims to address this gap by investigating the impact of collaborative learning, specifically structured to incorporate fundamental visual elements and principles (FVEVP), on students' comprehension and application in three-dimensional design—an essential area of design education. The study integrates an immersive design workshop with questionnaire surveys to evaluate student perceptions of the pedagogical strategy's effectiveness, advantages, and challenges. The findings demonstrate significant benefits of collaborative learning, including advanced learning processes, enhanced innovative thinking, elevated student confidence, and improved project efficiency, all attained cost-effectively. These benefits contribute to greater student satisfaction and superior educational results. Nonetheless, the study also highlights challenges, such as the unequal distribution of workloads and extended decision-making times, which emphasize the need for structured management strategies to bolster the educational effectiveness of collaborative learning. By providing critical insights into the intricate effects of collaborative learning in design education, the study offers valuable contributions to refining educational practices and directing future research.